2018 IEEE International Vacuum Electronics Conference (IVEC) 2018
DOI: 10.1109/ivec.2018.8391556
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of an insert cooling system for long-pulse operation of a coaxial-cavity gyrotron

Abstract: The successful operation of a 2 MW 170 GHz coaxial-cavity gyrotron has been demonstrated at IHM-KIT in short(ms) pulses and the ongoing research activities are aiming to upgrade the existing tube to the long-pulse regime. In this work, the performance of the insert cooling system is systematically studied for longpulse coaxial-cavity gyrotron operation. A multi-physics simulation model is developed with the relevant turbulence model and mesh parameters. The results suggest stable operation of the insert under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In parallel to the experimental investigations, multi-physics numerical simulations focused on the performance of the cooling system of the coaxial insert [17]. It was found that the existing water cooling can easily support even CW operation, by providing large margins both with respect to the ohmic loading of the insert and to a possible insert misalignment.…”
Section: Coaxial Gyrotron Technology At Longer Pulsesmentioning
confidence: 99%
“…In parallel to the experimental investigations, multi-physics numerical simulations focused on the performance of the cooling system of the coaxial insert [17]. It was found that the existing water cooling can easily support even CW operation, by providing large margins both with respect to the ohmic loading of the insert and to a possible insert misalignment.…”
Section: Coaxial Gyrotron Technology At Longer Pulsesmentioning
confidence: 99%